2020
DOI: 10.1186/s40348-020-0094-9
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of the nephron – a complex, vulnerable, and poorly explored backdrop for noxae impairing nephrogenesis in the fetal human kidney

Abstract: Background: The impairment of nephrogenesis is caused by noxae, all of which are significantly different in molecular composition. These can cause an early termination of nephron development in preterm and low birth weight babies resulting in oligonephropathy. For the fetal human kidney, there was no negative effect reported on the early stages of nephron anlage such as the niche, pretubular aggregate, renal vesicle, or comma-shaped body. In contrast, pathological alterations were identified on subsequently de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Although surprisingly, the analysis of pertinent literature further revealed that the role of the nephrogenic zone in the fetal human kidney in nephron formation and consequently as the primary target region for noxae impairing nephrogenesis has been hardly explored. Before this background, it is understandable that the contained stages of nephron anlage and the shaping of the nephron were only introduced over the past few years as the first systematic morphological information dealing with the specifics of the nephrogenic zone [ 8 10 ]. The results generated indicate that each stage of nephron anlage is the subject of an individual positioning, orientation, and shaping.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although surprisingly, the analysis of pertinent literature further revealed that the role of the nephrogenic zone in the fetal human kidney in nephron formation and consequently as the primary target region for noxae impairing nephrogenesis has been hardly explored. Before this background, it is understandable that the contained stages of nephron anlage and the shaping of the nephron were only introduced over the past few years as the first systematic morphological information dealing with the specifics of the nephrogenic zone [ 8 10 ]. The results generated indicate that each stage of nephron anlage is the subject of an individual positioning, orientation, and shaping.…”
Section: Introductionmentioning
confidence: 99%
“…Covered by the renal capsule, it is built up by transverse layers of embryonic, maturing, and matured parenchyma and stroma. In the external nephrogenic zone, the process of nephron formation starts [ 9 ] and can be recognized by the transient stages of nephron anlage [ 10 , 11 ]. In the subjacent maturation zone, the conversion of the S-shaped body as the last stage of nephron anlage into the lasting nephron occurs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations